Regulation of Alternative Polyadenylation by U1 snRNPs and SRp20 - Lou, Hua (American Society for Microbiology, 1998)
Although considerable information is currently available about the factors involved in constitutive vertebrate polyadenylation, the factors and mechanisms involved in facilitating communication between polyadenylation and splicing are largely unknown. Even less is known about the regulation of polyadenylation in genes in which 3′-terminal exons are alternatively recognized. Here we demonstrate that an SR protein, SRp20, affects recognition of an alternative 3′-terminal exon via an effect on the efficiency of binding of a polyadenylation factor to an alternative polyadenylation site. The gene under study codes for the peptides calcitonin and calcitonin gene-related peptide. Its pre-mRNA is alternatively processed by the tissue-specific inclusion or exclusion of an embedded 3′-terminal exon, exon 4, via factors binding to an intronic enhancer element that contains both 3′ and 5′ splice site consensus sequence elements. In cell types that preferentially exclude exon 4, addition of wild-type SRp20 enhances exon 4 inclusion via recognition of the intronic enhancer. In contrast, in cell types that preferentially include exon 4, addition of a mutant form of SRp20 containing the RNA-binding domain but missing the SR domain inhibits exon 4 inclusion. Inhibition is likely at the level of polyadenylation, because the mutant SRp20 inhibits binding of CstF to the exon 4 poly(A) site. This is the first demonstration that an SR protein can influence alternative polyadenylation and suggests that this family of proteins may play a role in recognition of 3′-terminal exons and perhaps in the communication between polyadenylation and splicing.